Physiological and biochemical responses of elevated ozone on Pterocarpus indicus under well-watered and drought conditions. Issue 4 (2nd October 2018) - Baek, Saeng Geul; Park, Jeong ho; Kwak, Myeong Ja; Lee, Jong Kyu; Na, Chae Sun; Lee, Byulhana; Woo, Su Young
Abstract: Seedlings of Pterocarpus indicus were grown in both well-watered and drought stress conditions in phytotron. Seedlings grown under well-watered and drought stress conditions were exposed to either combined or without ozone of 200 ppb for one month. First, the physiological responses to elevated ozone levels indicated a decreased biomass. The seedlings grown in arid soil and exposed to ozone showed less biomass than those grown in arid soil but not exposed to ozone. Moreover, all the seedlings except the well-watered and unexposed ones showed a significantly lower photosynthetic rate (PN ) over time. However, with the accumulation of ozone injuries, the antioxidant enzyme activities increased overall. In the study results, when exposed to ozone, the well-watered seedlings exhibited more antioxidative enzyme activity than did the seedlings grown in arid soil. Generally, P. indicus in arid soil suffered less damage from elevated ozone than did the well-watered plants.